Efficiency Effects of Fiscal Equalization on Economic Development - Islam, MD Nahidul (Curtin University, 2020)
This study develops a theoretical model to analyse the incentive effects of revenue-sharing fiscal equalization systems on regional economic development, in the context of a representative tax system. The key finding is that the presence of a fiscal equalization net transfer incentivises a region to select a suboptimal savings rate. This results in less accumulation of capital for future regional economic development.